Neonatal injury alters adult pain sensitivity by increasing opioid tone in the periaqueductal gray - LaPrairie, Jamie; Murphy, Anne Z. (Frontiers in Behavioral Neuroscience, 2009)
Studies in both rodents and humans have shown that acute inflammatory pain experienced during the perinatal period produces long-term decreases in pain sensitivity (hypoalgesia) (Grunau et al., 1994a; Grunau et al., 2001; Ren et al., 2004; LaPrairie and Murphy, 2007). To date, the mechanisms underlying these long-term adaptations, however, have yet to be elucidated. The present studies tested the hypothesis that neonatal inflammatory pain induces an upregulation in endogenous opioid tone that is maintained into adulthood, and that this increase in opiate tone provides the underlying mechanism for the observed hypoalgesia. On the day of birth (P0), inflammatory pain was induced in male and female Sprague-Dawley rats by intraplantar administration of carrageenan (CGN; 1%). In adulthood (P60), these animals displayed significantly increased paw withdrawal latencies in response to a noxious thermal stimulus in comparison to controls. Systemic administration of the brain-penetrant opioid receptor antagonist Naloxone HCl, but not the peripherally-restricted Naloxone Methiodide, significantly attenuated the injury-induced hypoalgesia. Direct administration of Naloxone HCl or antagonists directed at the mu or delta opiate receptors into the midbrain periaqueductal gray (PAG) also significantly reversed the injury-induced hypoalgesia in adult rats. Parallel anatomical studies revealed that inflammatory pain experienced on the day of birth significantly increased beta-endorphin and met/leu-enkephalin protein levels and decreased opioid receptor expression in the PAG of the adult rat. Thus, early noxious insult produces long-lasting alterations in endogenous opioid tone, thereby profoundly impacting nociceptive responsiveness in adulthood.